The LatHyS database for planetary plasma environment investigations: Overview and a case study of data/model comparisons. (January 2018) - Modolo, R.; Hess, S.; Génot, V.; Leclercq, L.; Leblanc, F.; Chaufray, J.-Y.; Weill, P.; Gangloff, M.; Fedorov, A.; Budnik, E.; Bouchemit, M.; Steckiewicz, M.; et al.
Abstract: We present the Latmos Hybrid Simulation (LatHyS) database, which is dedicated to the investigations of planetary plasma environment. Simulation results of several planetary objects (Mars, Mercury, Ganymede) are available in an online catalogue. The full description of the simulations and their results is compliant with a data model developped in the framework of the FP7 IMPEx project. The catalogue is interfaced with VO-visualization tools such AMDA, 3DView, TOPCAT, CLweb or the IMPEx portal. Web services ensure the possibilities of accessing and extracting simulated quantities/data. We illustrate the interoperability between the simulation database and VO-tools using a detailed science case that focuses on a three-dimensional representation of the solar wind interaction with the Martian upper atmosphere, combining MAVEN and Mars Express observations and simulation results. Abstract : Highlights: A simulation database dedicated to planetary plasma environments. Relevance and importance of meta-data and VO tools in the advancement of scientific research. Illustration of combined simulation and observation datasets in the Martian plasma environment.